Contemporary Approaches to Halal and Sustainable Eco-Tourism: A Study of Community-Based Tourism in Ganoang and Puncak Mas - Muslimin; Dede Aji Mardani; Aja Rowikarim; Rusani Jaelani; Fatimah Kacem (MILRev: Metro Islamic Law Review, 2025)
Tourism is a vital industry that creates job opportunities and allows for economic development in the halal tourism sector. Tasikmalaya and Bandar Lampung are two regions in Indonesia that can be potentially developed for nature-mountain tourism, with Mount Ganoang and Puncak Mas as the natural assets. This research identifies the potential of Mount Ganoang and Puncak Mas as sustainable and community-based ecotourism by employing a descriptive method with qualitative analysis techniques and a legal anthropological approach. Primary data was collected through interviews, observations, and field measurements. The results show that based on the tourism suitability index, the physical conditions of Mount Ganoang and Puncak Mas carry the potential adequate for development through improved management and human resources as community-based halal ecotourism. Halal ecotourism, which presents nature as a destination, supports the economic circulation of the community with many people involved in economic activities from tourism despite basic differences in capital, ownership, and juridical aspects (Local Regulation concerning Values No.7 of 2014 and Lampung Provincial Regulation No. 2 of 2008 concerning the Preservation of Lampung Culture. This research offers a strategic recommendation for developing sustainable and inclusive halal ecotourism models that respect local regulations and cultural values in Tasikmalaya and Bandar Lampung.